Arts in a knowledge-based economy : activist strategies in Singapore's Renaissance - Woon, Tien Wei (Curtin University, 2012)
The topic of this thesis is the response by the Singaporean arts community to sudden and dramatic changes in government planning policy, in particular, the Renaissance City Plan (RCP), introduced in 2000. This plan provided the vision to transform Singapore into a vibrant global city of the arts as part of a move towards a Knowledge-based Economy. Although providing increased funding for the arts in Singapore, the policy changes appeared to some aspects of the arts community to be purely economically driven. This thesis argues that community-led cultural development are important for building a vibrant art scene and cultural development should not be left entirely up to government cultural planners.To allow an understanding of the different motivations that drive government-led and community-led cultural initiatives, this thesis establishes an economic, political and social history of Singapore, and its relationship to the arts. This thesis adopts the term ‘artist/cultural activist’ to describe those artists who develop community-led art practices, undirected by government policy.Case studies are presented of the collectives The Artists Village and Post-Museum, as well as the work of artist Koh Nguang How. Further, the author uses his own art practice as a means to reflect on the process and experiences of those whose cultural activist motivations give a 'community-led cultural development' character to their practice. Both to archive this work, and to demonstrate collective, ephemeral art practice, the author has included a digital artwork titled ‘Server Foundation: Indexes’.The thesis adopts Bourriaud’s notion of 'everyday micro-utopias' to describe the practice of artists that uses social relations as both the form and content of their artworks (Bourriaud 1998, 27), and contextualises this practice in the context of Singapore's Renaissance, showing cultural activism as a form of art practice which is making significant contributions to art practice and history in Singapore. It finds that a non-government, cultural activist-initiated contribution is critical to achieve a healthy progression of Singapore's Renaissance.This thesis concludes with the proposition that practices and artistic strategies of the artist/cultural activist should not be seen simplistically as a 'position of resistance', but as providing a valuable, even critical, contribution towards Singapore's Renaissance.